Orbital lipoma - Nabajyoti Borah; Inamul Haque Haque; Navanil Barua; Ananya Barman; Sneha Gang; Shabnam Akhtar Ahmed (Romanian Neurosurgery, 2023)
Orbital lipomas are uncommon benign tumors with only a few reported cases in literature.  They are usually asymptomatic and exhibit gradual growth.  We rendered such a rare case of primary lipoma in the orbital region with interpreted symptoms of ocular pain, reduced vision, and mild proptosis.  Right fronto-orbital craniotomy with gross total excision of the tumor was done.  Histological examination suggested a final diagnosis of lipoma.  Post-operatively, the patient developed mild ptosis.  During follow-up, ptosis completely subsided and significant improvement in vision was noted.